Gendered Paradoxes in Shōnen Anime: A Visual Narrative Study of Character Design and Fandom Reception of Sakura Haruno and Nami - Rizky Ananta Saputra; Muhammad Fathoni; Ni Putu Sinta Dewi (Journal of Innovative and Creativity, 2026)
The purpose of the study was to investigate the representation of female characters in popular shōnen anime across different generations by examining Sakura Haruno (Naruto) and Nami (One Piece). Both characters occupy central narrative positions yet elicit paradoxical responses within international fandoms. The materials analyzed comprised the visual and narrative texts of the selected anime series, as well as audience reception data drawn from digital fan communities. A qualitative descriptive methodology was employed, utilizing a visual narrative approach informed by Greimas’s narrative theory, Laura Mulvey’s feminist theory of representation, postfeminist perspectives, and Edwards’s narrative framework. Data were collected through close visual analysis of character design, narrative functions, expressive behaviors, and visual framing, alongside interpretative analysis of fandom discourse across online platforms. The results demonstrate that the representations of Sakura Haruno and Nami are characterized by narrative dissonance, particularly stemming from the tension between their heroic contributions and their recurrent deployment as comedic figures or objects of visual emphasis. This dissonance contributes to fragmented and polarized audience interpretations at the global level. The study concludes that female character representation in shōnen anime remains significantly shaped by gendered narrative structures and patriarchal visual conventions, which continue to influence patterns of reception and debate within international fandom cultures.